The Effect of Share Tenancy on Rice Productivity in Kulon Progo Regency - Waluyati, Lestari Rahayu; Fatimah, Zuhriyyah Hasna Nur (SOCA: Jurnal Sosial Ekonomi Pertanian, 2025)
Variations in land ownership status, such as self-owned land, rental farming, and profit-sharing system, are believed to influence the productivity of rice farming. In Kulon Progo Regency, the shrinking agricultural land area due to infrastructure development, rising price of farm land’s rent, along with an increasing number of farmers without land’s ownership, highlights the urgency of examining the effectiveness of the profit-sharing system. However, empirical evidence regarding its impact on productivity remains limited. This research is aimed to study whether the profit-sharing system achieves similar productivity levels compared to self-owned or rented land. In this research, proportional stratified random sampling is utilized as the main method of acquiring data samples. There are 92 respondents studied in this research. Descriptive quantitative analysis and double linear regression analysis of Cobb-Douglas production function were employed as methods of analysis in this study. The result showed there was no difference in level of productivity between self-owned land farming and rental farming. Fertilizer use and farming experience were found as factors that increase productivity in rice farming, while land area and labor were found as factors that decrease productivity. These findings support Cheung’s theory, which asserts that there is no difference in productivity between profit-sharing and fixed-rent systems. Moreover, the results offer practical insights, suggesting that non-ownership land management, such as rental and profit-sharing, can serve as viable alternatives to improve land accessibility in the agricultural sector, particularly for young farmers.